2007
DOI: 10.1088/0957-4484/18/47/475709
|View full text |Cite
|
Sign up to set email alerts
|

The hydrodynamic size of polymer stabilized nanocrystals

Abstract: For many emerging applications, nanocrystals are surface functionalized with polymers to control self-assembly, prevent aggregation, and promote incorporation into polymer matrices and biological systems. The hydrodynamic diameter of these nanoparticle–polymer complexes is a critical factor for many applications, and predicting this size is complicated by the fact that the structure of the grafted polymer at a nanocrystalline interface is not generally established. In this work we evaluate using size-exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…In addition to the NP's intrinsic properties, agglomeration depends also on the composition of the dispersing medium, and thus measurements of hydrodynamic diameters should always be performed in the biological medium in which they are studied ( Figure ). For the determination of hydrodynamic diameters (of single NPs in case of no agglomeration, and of the agglomerate size in case of agglomeration) many different methods exist, though all need to be interpreted differently, as they are based on different detection principles. Dynamic light scattering (DLS) is probably the most frequently used technique for determining hydrodynamic diameters, as commercial machines are easily available in many laboratories.…”
Section: Physico‐chemical Parameters That Matter At the Nanoscalementioning
confidence: 99%
“…In addition to the NP's intrinsic properties, agglomeration depends also on the composition of the dispersing medium, and thus measurements of hydrodynamic diameters should always be performed in the biological medium in which they are studied ( Figure ). For the determination of hydrodynamic diameters (of single NPs in case of no agglomeration, and of the agglomerate size in case of agglomeration) many different methods exist, though all need to be interpreted differently, as they are based on different detection principles. Dynamic light scattering (DLS) is probably the most frequently used technique for determining hydrodynamic diameters, as commercial machines are easily available in many laboratories.…”
Section: Physico‐chemical Parameters That Matter At the Nanoscalementioning
confidence: 99%
“…There, it was demonstrated that SEC of CdS QDs stabilized with alkanethiols, in THF containing 1 mmol L −1 Cd(ClO 4 ) 2 + 1 mmol L −1 dodecanethiol, is feasible. Later studies by Wilcoxon and Provencio [37], Wang et al [39], and Kruger et al [36,38] have shown how SEC reveals various characteristics and size-dependent properties of CdSe and CdSe/ZnS core/shell nanocrystals, as described below.…”
Section: Organic Sec Characterization Of Npsmentioning
confidence: 99%
“…[36,38] were able to employ SEC with toluene containing 0.1 mol L −1 trioctylphosphine for the hydrodynamic size determination of polystyrene- and alkythiol-coated CdSe nanocrystals. Polystyrene standards were used for size calibration of the SEC column.…”
Section: Organic Sec Characterization Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this difference in organic layer thickness between the two QDs examined could, possibly, be due to a difference in “grafting density” of octadecylamine, with a lower density in QD 510 than in QD 620. High packing density is known to restrict the movement of polymer chains, leading to more extended conformation than when the packing density is lower [20, 21]. It should be noted, however, that both these values for the size of the alkyl layer appear to be quite reasonable.…”
Section: Resultsmentioning
confidence: 99%